Statistical Study of Magnetic Topology for Eruptive and Confined Solar Flares. Issue 3 (7th March 2018) - Cui, Yanmei; Wang, Haimin; Xu, Yan; Liu, Siqing
Abstract: Large flares and halo coronal mass ejections (CMEs) can often cause strong space environment disturbances and sequently a series of space environment effects. The X‐class flares associated with halo CMEs are particular prone to these effects. In this paper, 58 X‐class flares were collected and studied with the source locations in 30° from the disk center, which were observed from 1996 to 2015. Among these events, 48 flares were associated with CMEs and defined as "eruptive" events. The other 10 flares without CMEs were defined as "confined" flares. By comparing the properties of flares and associated magnetic fields for the two sets of samples, we found the following: (1) magnetic free energy and overlying transverse fields play important roles in producing solar eruptions. Eruptive flares with high‐speed CMEs tend to occur in active regions with more free energy and larger decay index. (2) CME speeds are affected by magnetic free energy, which are described by parameters of the unsigned magnetic flux, the area of polarity inversion region, and the strength of transverse fields in the low altitude. These parameters have moderate positive correlations with CME speeds. Key Points: Eruptive and confined flares have been statistically studied on their properties of magnetic topology Solar eruptions are determined by magnetic free energy and overlying transverse field decay Eruptive flares associated with high‐speed CMEs tend to occur in the active regions with more free energy and larger decay index